PENEGASAN DAN PENGUATAN MAKNA PADA HEADLINE BERITA TVONENEWS - Sari, Suci Rahmah; Ernawati, Yeni (LPPM Universitas PGRI Silampari Lubuklinggau, 2023)
Abstract This research aims to describe the use of dysphemia and euphemism in tvOneNews headlines. The theory used as a reference by the researcher is Chaer's theory (2013). Chaer's theory states that there are causative factors that affect meaning change, namely there are 5 types of meaning change including widening, narrowing, euphemia, dysphemia, and total change. The research method used is qualitative with a case study approach. The data source taken is in the form of news headlines on tvOneNews Investigation and Crime: